POTENSI BELERANG DARI BOKASHI ECENG GONDOK Eichhornia crassipes (Martt.)Solm DALAM MENINGKATKAN MUTU SERTA HASIL PADI PADA INCEPTISOLS - Emma Trinurani Sofyan (Universitas 17 Agustus 1945 Samarinda, 2014)
Sulphur Potential of Water Hyacinth Eichhornia crassipes (Martt.) Solm Bokashi in Improving The Quality and Yield of Rice in Inceptisols. The objectives of research were to find out sulphur potential of hyacinth bokashi in improving the quality and yield of rice in Inceptisols. The experiment was conducted from April 2012 to October 2012 in a Greenhouse of Faculty of Agriculture, Padjadjaran University, Subdistrict Jatinangor, Regency Sumedang, West Java Province, at elevation of 782 m above sea level. Randomized Block Design (RBD) was used factorial pattern and repeated three times. The first factor was the dosage of sulphur (S) fertilizer consisted of : without S fertilizer; 20; 40; and 60 kg ha-1 S fertilizer, and the second factor was dosage of water hyacinth bokashi (B) consisted of: without bokashi; 15; 30; and 45 t ha-1 bokashi. Water hyacinth Eichhornia crassipes (Martt.) Solm bokashi is a superior organic matter with an excess of element sulphur. The preliminary experiment result interaction between sulphur fertilizer and water hyacinth bokashi on total S, available SO42-, total N, C-organic, available P, Zn, uptake S, N and yield effect occurred between give an uptake P but not significant on Fe and uptake P. The independent influence sulphur fertilizer and water hyacinth bokashi effect on soil availableP. The analysis respons optimum dosage of sulphur was 45.52 kg ha-1 and bokashi water hyacinth was 35.99 t ha-1 to yield of rice plat obtained was 9.27 t ha-1. Multiple regretion between respons parameters with yield of rice plant obtained was available P, uptake P, and available SO42-, gave efffect to yield and R2 = 0.70**, 70 percent gave significant contributions to yield by available P, uptake P, and available SO42 on Inceptisols.